Promosi Dan Penyuluhan Kesehatan Reproduksi Remaja Dan Bahaya Kehamilan Diluar Nikah Dalam Komunitas - Primasari, Sefria Indah; Reghita, Sivana Gian (Devotion: Journal Corner of Community Service, 2024)
Indonesia is a country with a relatively high rate of early marriage compared to other countries, so it will indirectly be filled with various problems, including reproductive health. Reproductive health is an important aspect in developing the quality of future generations. Through the community service program in the form of reproductive health education activities, it is hoped that it can contribute to increasing understanding of reproductive health and marriage age for teenagers at SMP N 2 Bekri, Central Lampung. The method used in this activity is promotion and providing counseling on adolescent reproductive health and the dangers of extraneous pregnancy. marry in the community. The results of the service activities showed that the participants were able to understand the importance of reproductive health from an early age and participated actively in outreach activities. This can be seen from the percentage of participant attendance of more than 70%. Participants also gave positive responses to the outreach activities. Thus, community service activities in the form of reproductive health education can: 1) increase teenagers' understanding regarding reproductive health; 2) the emergence of adolescent awareness regarding the ideal marriage age; and 3) extension activities run effectively